The Interplay of Sustainability, Constitutionalism and Legitimacy: Examining the “Political Ecotopia” as a manifestation of Social Sustainability and a Pillar of Constitutionalism - Treneska-Deskoska, Renata; Trajkovska-Hristovska, Jelena (Societatea de Stiinte Juridice si Administrative, 2024)
The three main pillars of sustainability are environment, economy, and society. Society, as a component of sustainability, represents a category that is particularly difficult to explain and analyze. This category encompasses a range of values, ideas, and concepts that are widely accepted and desired. Among these, the concepts of constitutionalism and legitimacy are key legal and political constructs that underpin social sustainability. Conversely, legitimacy is a crucial element that ensures the sustainability of constitutionalism. This paper will explore several key questions: Is legitimacy a conditio sine qua non for constitutionalism? Is legitimacy a dynamic and sustainable category? Does legitimacy embody a value that is inherently desirable and beneficial? The study will further examine whether maintaining legitimacy incurs costs and if it is necessary to invest in sustaining this dynamic category. Finally, the paper will discuss whether the idea of legitimacy, as a sustainable resource for constitutionalism, is a necessity or merely a political "ecotopia."
Keywords: social sustainability, constitutionalism, legitimacy, sustainability, the right to rule, limited government, political system